Marketing the intrinsic quality of the product - Young J.A. (Global quality assessment in Mediterranean aquaculture, 2000)
The paper, after beginning by establishing the context of different perspectives on quality, contends that delivery of quality must be driven by consumer considerations because the quality perceived in different market segments is the determinant of future consumption. Delivery of quality perceived desirable demands answers to questions surrounding the marketing of product quality. The fundamental marketing tasks of generating information about quality values, their creation, communication and consistently are outlined. The market research process is discussed in the context of identifying consumers' wants and the competition. This process determines product quality goals and positioning in target markets. Next is the creation of the product which is the carrier of the quality values. Product range decisions, including positioning and new product development are established as the backdrop to the creative process.
Workshop of the CIHEAM Networks on Technology of Aquaculture in the Mediterranean (TECAM) and Socio-Economic and Legal aspects of Aquaculture in the Mediterranean, 1999/11/29-1999/12/01, Barcelona (Spain)